Tax Influence on Financial Structures of M&As - Christoph Harendt (ZBW - Leibniz-Informationszentrum Wirtschaft, 2018)
A well-known strategy of tax avoidance by multinationals is to locate debt in subsidiaries in countries with a high tax rate. In case of M&As it is particularly advantageous to locate debt at the level of holdings. By using firm-level data provided by the German Central Bank, I show empirically that indeed the probability that a firm is held by a holding in the same country increases with the local tax rate. Furthermore, consolidating the balance sheets of firms and their holdings leads to a stronger effect of taxes on the debt ratio. However, I find this effect only for a sample of all firms and no additional effect in case of M&As. I conclude that those findings may be one explanation why previous studies have found relatively low effects of taxes on debt financing.
Keywords: F23; G32; G34; H25; H26; H32; 330; Corporate Taxation; Multinational Entities; Foreign Direct Investment; Capital structure; Mergers and acquisitions; Empirical Analysis; Firm-level data